Implementation of the ‘Optimising the Health Extension Program’ Intervention in Ethiopia: A Process Evaluation Using Mixed Methods - Okwaraji, Yemisrach B. (Int J Environ Res Public Health, 2020)
An intervention called ‘Optimising the Health Extension Program’, aiming to increase care-seeking for childhood illnesses in four regions of Ethiopia, was implemented between 2016 and 2018, and it included community engagement, capacity building, and district ownership and accountability. A pragmatic trial comparing 26 districts that received the intervention with 26 districts that did not found no evidence to suggest that the intervention increased utilisation of services. Here we used mixed methods to explore how the intervention was implemented. A fidelity analysis of each 31 intervention activities was performed, separately for the first phase and for the entire implementation period, to assess the extent to which what was planned was carried out. Qualitative interviews were undertaken with 39 implementers, to explore the successes and challenges of the implementation, and were analysed by using thematic analysis. Our findings show that the implementation was delayed, with only 19% (n = 6/31) activities having high fidelity in the first phase. Key challenges that presented barriers to timely implementation included the following: complexity both of the intervention itself and of administrative systems; inconsistent support from district health offices, partly due to competing priorities, such as the management of disease outbreaks; and infrequent supervision of health extension workers at the grassroots level. We conclude that, for sustainability, evidence-based interventions must be aligned with national health priorities and delivered within an existing health system. Strategies to overcome the resulting complexity include a realistic time frame and investment in district health teams, to support implementation at grassroots level.